Physically based rendering from theory to implementation - Pharr, Matt (Elsevier/Morgan Kaufmann, 2004)
"Computer graphics, and rendering in particular, is full of beautiful theory. The theory covers physical concepts, such as light fields and the interaction of light with different materials, and mathematical concepts, such as integral equations and Monte Carlo integration. The great thing about computers is that they allow us to build rendering systems based on the best theory. This book turns the theory of image-making into a practical method for creating images." from the foreword by Pat Hanrahan, Canon USA Professor, Stanford University From movies to video games, computer-rendered images are pervasive today. Physically Based Rendering introduces the concepts and theory of photorealistic rendering hand in hand with the source code for a sophisticated renderer. By coupling the discussion of rendering algorithms with their implementations, Matt Pharr and Greg Humphreys are able to reveal many of the details and subtleties of these algorithms.
Includes bibliographical references (pages 961-988) and indexes
Keywords: Infographie; COMPUTERS / Image Processing; PHOTOGRAPHY / Techniques / Digital; TECHNOLOGY & ENGINEERING / Imaging Systems; COMPUTERS / Digital Media / Graphics Applications; Computer graphics; Dreidimensionale Computergrafik; Rendering; Softwareentwicklung; Geometrische Modellierung; Realistische Computergrafik; Computergrafik; Metamathematik